The Modulatory Role of CYP3A4 in Dictamnine-Induced Hepatotoxicity - Li, Zhuo-Qing; Jiang, Li-Long; Zhao, Dong-Sheng; Zhou, Jing; Wang, Ling-Li; Wu, Zi-Tian; Zheng, Xian; Shi, Zi-Qi; Li, Ping; Li, Hui-Jun (Frontiers in Pharmacology, 2018)
Dictamni Cortex (DC) has been reported to be associated with acute hepatitis in clinic and may lead to a selective sub-chronic hepatotoxicity in rats. Nevertheless, the potent toxic ingredient and the underlying mechanism remain unknown. Dictamnine (DTN), the main alkaloid from DC, possesses a furan ring which was suspected of being responsible for hepatotoxicity via metabolic activation primarily by CYP3A4. Herein, the present study aimed to evaluate the role of CYP3A4 in DTN-induced liver injury. The in vitro results showed that the IC50 values in primary human hepatocytes (PHH), L02, HepG2 and NIH3T3 cells were correlated with the CYP3A4 expression levels in corresponding cells. Furthermore, the toxicity was increased in CYP3A4-induced PHH by rifampicin, and CYP3A4 over-expressed (OE) HepG2 and L02 cells. Contrarily, the cytotoxicity was decreased in CYP3A4-inhibited PHH and CYP3A4 OE HepG2 and L02 cells inhibited by ketoconazole (KTZ). In addition, the hepatotoxicity of DTN in enzyme induction/inhibition mice was further investigated in the aspects of biochemistry, histopathology, and pharmacokinetics. Administration of DTN in combination with KTZ resulted in attenuated liver injury, including lower alanine transaminase and aspartate transaminase activities and greater AUC and Cmax of serum DTN, whereas, pretreatment with dexamethasone aggravated the injury. Collectively, our findings illustrated that DTN-induced hepatotoxicity correlated well with the expression of CYP3A4, namely inhibition of CYP3A4 alleviated the toxicity both in vitro and in vivo, and induction aggravated the toxicity effects.